Perspective On The Efficacy Of Industrialized Building System In Civil Engineering Curriculum - Atique, Sumra; Khan, Jam Shahzaib; Zakaria, Rozana; Sattar, Aisha; Soomro, Mohsin Ali; Aminudin, Eeydzah; Izieadiana, Nur; Shamsuddin, Siti Mazzuana (Tropical Scientific Journal, 2024)
Objective: Industrialized Building System (IBS) refers to a technique of constructing and manufacturing components in a controlled environment, onsite/offsite. In Malaysia, IBS is strongly supported by government at due to its versatilities in various ways and techniques. However, the application of IBS still faces challenges in lack of technical expertise or professional workers. Based on the new IBS roadmap 2030, one of the new pillars is needed to have a ready pool of components for IBS professionals and workers throughout the entire project lifecycle. Therefore, students related to construction and engineering need an early exposure to the application of IBS in Malaysia to provide a platform for readiness of IBS application in construction industry. This study aims to identify the effectiveness of IBS curriculum in Civil Engineering courses; thus, the investigation seeks the agreement of Civil Engineering student on the curriculum offers and later comparison study is made on the effectiveness of IBS curriculum within the research, technical and polytechnic Higher Learning Institutions (HLI’s). Research Method: For this research, a questionnaire survey was employed amongst three HLI’s involving final year students. The data was analyzed using frequency analysis and average index. Findings: The studies and findings shows deficit of IBS curriculum in HLI’s. Originality: This study will help in improving the strategies and action plans in higher education institution curriculum based on technical knowledge and skill in IBS.